Pengaruh Kombinasi Ekstrak Daun Singkong dan Singkil terhadap Serangan Hama Kangkung Darat - Ginting, Selvia Teodora Br; Lumowa, Sonja V. T.; Masitah, Masitah; Makkadafi, Suparno Putera (Biocaster : Jurnal Kajian Biologi, 2025)
This study aims to test the effectiveness of the combination of cassava leaf extract Adira 1 (Manihot esculenta Crantz) and singkil leaves (Premna pubescens Blume) as a botanical pesticide against the intensity of insect pest attacks on land spinach (Ipomoea reptans Poir). The study was conducted from March to April 2025 in Girimukti Village, Penajam District, Penajam Paser Utara Regency. This study used an experimental method with a one-factor Completely Randomized Design (CRD) consisting of five concentration treatment levels (0%, 20%, 35%, 50%, and 65%), each repeated five times, so that there were 25 experimental units. The parameters observed were the level of leaf damage due to pest attacks which were measured weekly. Data were analyzed using one-way Analysis of Variance (ANOVA), and continued with the Least Significant Difference (LSD) test at a significance level of 5%. The results of the analysis showed that the extract concentration treatment had a significant effect on reducing the intensity of pest attacks. Treatment with a concentration of 65% showed the highest effectiveness in reducing leaf damage due to pest attacks compared to other treatments. The conclusion of this study is that the combination of cassava leaf extract and singkil leaf has the potential to be an effective botanical pesticide and can be an alternative to chemical pesticides in sustainable agricultural systems.